Structural modeling of HLA-B*1502/peptide/carbamazepine/T-cell receptor complex architecture: implication for the molecular mechanism of carbamazepine-induced Stevens-Johnson syndrome/toxic epidermal necrolysis. Issue 8 (2nd August 2016) - Zhou, Peng; Zhang, Shilei; Wang, Yewang; Yang, Chao; Huang, Jian
Abstract : Drug-induced adverse reactions are a significant problem in healthcare worldwide and are estimated to cost billions of dollars annually in the United States. A portion of such reactions is observed to strongly associate with certain human leukocyte antigen (HLA) alleles; one of the strongest associations is the HLA-B*1502 protein with carbamazepine (CBZ)-induced Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) – the odds ratio value can even be higher than one thousand. The particularly strong association in CBZ-induced SJS/TEN suggests that the HLA-B*1502 is not only a genetic marker but also a participant in the pathogenesis of the disease. In the current study, we attempt to computationally model the atomic-level structure of the complete HLA-B*1502/peptide/CBZ/T-cell receptor (TCR) complex architecture based on prior knowledge obtained from epidemiological investigations as well as in vitro and in vivo assays. The model tells a different story about the molecular mechanism of CBZ-induced SJS/TEN from that previously reported for abacavir (ABC)-induced hypersensitivity (HSR); the CBZ molecule is located at the interface between HLA-B*1502/peptide and TCR, directly contacts the P3–P6 residues of antigen peptide, and bound within a pocket region encompassed by two TCR CDR3 fingers. Molecular dynamics simulation and binding energy analysis further reveal that the CBZ shows considerably high affinity to TCR over HLA-B*1502/peptide, which can tightly interact with the former rather than the latter. From the model, two hypotheses are proposed that can well explain most previous observations and are expected to guide next wet-lab experiments. This study could help to promote our understanding of the molecular mechanism and pathological implication underlying CBZ-induced SJS/TEN.